Crop-Zone Weed Mycobiomes of the South-Western Australian Grain Belt - Michael, Pippa J.; Jones, Darcy; White, Nicole; Hane, James K.; Bunce, Michael; Gibberd, Mark (Frontiers in Microbiology, 2020)
In the absence of a primary crop host, secondary plant hosts may act as a reservoir for fungal plant pathogens of agricultural crops. Secondary hosts may potentially harbor heteroecic heteroecious biotrophs (e.g. the stripe rust fungus Puccinia striiformis) or other pathogens with broad host ranges. Agricultural grain production tends towards monoculture or a limited number of crop hosts over large regions, and local weeds are a major source of potential secondary hosts. In this study the fungal phyllospheres of 12 weed species common in the agricultural regions of Western Australia (WA), were compared through high-throughput DNA sequencing. Amplicons of D2 and ITS were sequenced on an Illumina MiSeq system using previously published primers and BLAST outputs analyzed using MEGAN. A heatmap of cumulative presence-absence for fungal taxa was generated and variance patterns investigated using PCA and CCA. We observed the presence of several major international crop pathogens, including basidiomycete rusts of the Puccinia spp., and ascomycete phytopathogens of the Leptosphaeria and Pyrenophora genera. Unrelated to crop production, several endemic pathogen species including those infecting Eucalyptus trees were also observed, which was consistent with local native flora. We also observed that differences in latitude or climate zones appeared to influence the geographic distributions of plant pathogenic species more than the presence of compatible host species, with the exception of Brassiceae host family. There was an increased proportion of necrotrophic Ascomycete species in warmer and drier regions of central WA, compared to an increased proportion of biotrophic Basidiomycete species in cooler and wetter regions in southern WA.